Studying Cytotoxic T-lymphocyte- Associated Antigen-4 (CTLA-4) gene Polymorphism in a Sample of Iraqi Women with Polycystic Ovarian Syndrome - Haneen Subhee Shaheed; Wassan Abdul-Kareem Abbass; Suzan Yousif Jasim (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2019)
Polycystic ovarian syndrome (PCOS) considers as the most common disorder among women during reproductive age. Its common features involve hyperandrogenism, chronic anovulation, and weight gain. Till now, the pathogenesis of PCOS stay unknown, and